Pengendalian Kualitas Terhadap Aksesoris Kulit Menggunakan Pendekatan Statistical Quality Control (SQC) Dan Fuzzy Analytical Hierarchy Process (F-AHP) - Ricky Novan Pradhana; Elly Wuryaningtyas Yunitasari; Syamsul Ma’arif (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2023)
Abekani Leather is a company engaged in the manufacture of leather accessories made from cowhide. In running its business, abekani leather uses the Make To Stock (MTS) and Make To Order (MTO) systems to meet market needs. In running its business, Abekani Leather is constrained by the number of defective products reaching an average of 5% for the period June-December 2021. The purpose of this study is to find out whether the product defect is still within the limits of the control, the factors that can affect, and suggestions for major improvements..This study uses the Statistical Quality Control (SQC) method which aims to statistically control the quality, and the Fuzzy Analytical Hierarchy Process (F-AHP) to determine the main improvement suggestions. After doing the research, the results obtained are, abekani leather accessories products are still under statistical control, which is indicated by the absence of out of control data on the U map with center line 0.0543. The cause of product defects is influenced by several factors, including Human Factors, Machine Factors, Method Factors and Material Factor. The main improvement suggestion is to hold regular meetings every month to discuss improving the quality of leather accessories products with a score of 0.7459.